Projecting advanced enterprise network and service management to active networks. - Boutaba, R.
Active networks is a promising technology that allows us to control the behavior of network nodes by programming them to perform advanced operations and computations. Active networks are changing considerably the scenery of computer networks and, consequently, affect the way network management is conducted. Current management techniques can be enhanced and their efficiency can be improved, while novel techniques can be deployed. This article discusses the impact of active networks on current network management practice by examining network management through the functional areas of fault, configuration, accounting, performance and security management. For each one of these functional areas, the limitations of the current applications and tools are presented, as well as how these limitations can be overcome by exploiting active networks. To illustrate the presented framework, several applications are examined. The contribution of this work is to analyze, classify, and assess the various models proposed in this area, and to outline new research directions
Keywords: Accounting; Active networks; Computer networks; Configuration management; Enterprise network management; Enterprise service management; Fault management; Network nodes programming; Network performance; Research